The cost of rehabilitation after critical illness: a comparison of hospitalization costs for traumatic brain injury and non-traumatic brain injury patients with disorders of consciousness - Yu, Miao; Huang, Zhongmou; Yang, Yansui; Wang, Yulin; Ren, Hai; Tang, Shilan (Frontiers in Public Health, 2025)
BackgroundThis study aims to compare hospitalization costs between traumatic brain injury (TBI) and non-traumatic brain injury (non-TBI) patients with disorders of consciousness (DoC) to explore cost determinants.MethodsA retrospective analysis was conducted on 210 DoC inpatients admitted to Shenzhen Longcheng Hospital, a tertiary rehabilitation hospital located in China’s Pearl River Delta region, between 2015 and 2020. Patients were categorized into TBI (n = 44) and non-TBI (n = 166) groups based on etiology. Demographic, clinical, and hospitalization cost data were collected for each patient. The study compared the cost composition for DoC patients by etiology and used multivariate analysis to identify factors influencing hospitalization costs.ResultsThe median length of stay (LOS) and cost for TBI patients were 363.5 days and $57,366.05, respectively, while for non-TBI patients, the medians were 280.5 days and $57,117.64. Across both groups, the highest cost components were rehabilitation, medication, and treatment expenses. Factors associated with higher hospitalization costs included non-TBI etiology, local residents, medical insurance, LOS, self-employed, surgical treatment, and traditional Chinese medicine (TCM) intervention.ConclusionHospitalization cost structures were similar across etiologies, emphasizing value-driven care priorities. Key factors associated with higher hospitalization costs included non-TBI etiology, local residency, medical insurance, LOS, self-employment status, surgery, and TCM. These findings highlight key drivers of healthcare costs in DoC care, emphasizing the need for targeted policy interventions. However, given the limitations of this study, further research with larger, more diverse samples is essential to comprehensively assess the impact of costs on patient outcomes and care quality.